Mottos Of Opposition Movements In Iraq During The Umayyad Period and Their Religious and Political Indications (Journal of the College of Education for Women, 2019)
Mottos Of Opposition Movements In iraq during the umayyad period and their religious and political indications - al shia and al khawarij